GENDER DIFFERENCES IN THE EFFICACY OF RISK FACTORS CORRECTION AND TREATMENT COMPLIANCE IN PATIENTS AFTER ACUTE CORONARY SYNDROME - A. Y. Efanov; D. F. Nizamova; E. F. Dorodneva; I. V. Medvedev; S. V. Shalaev (Рациональная фармакотерапия в кардиологии)
Aim. To compare the efficacy of correction of modifiable risk factors for ischemic heart disease (IHD), and treatment compliance within 6 months of observation in group of men and group of women after acute coronary syndrome (ACS). Material and мethods. Patients (n=147: 100 men and 47 women) aged under 70 years who underwent ACS were examined. Prevalence of cardiovascular risk factors and frequency of basic drugs taking were evaluated at baseline and after 6 months. The efficacy of risk factors correction in men was compared with this in women. Results. A general number of patients with effective blood pressure (BP) control as well as patients who reached the target levels of total cholesterol (TC) <4.5 mmol/l and cholesterol of low>density lipoproteins (LDC) <2.5 mmol/l after 6 months increased significantly in comparison with this before observation. Taking of drugs from all main groups left unsatisfactory and did not>reach the advisable values. Women have better antihypertensive treatment compliance, but worse lipidemia level control; they more often have glucose metabolism disorders, arterial hypertension and obesity. Men smoked more often, but have better BP, TC and cholesterol LDC control. Conclusion. The high prevalence of cardiovascular risk factors requires intensification of preventive activity regarding IHD onset and progression among both men and women.